MUSHTARAK IJTIMOIY MUHIT VA KOMMUNIKATIV YAXLITLIKDA TILLAR O‘ZARO TA’SIRI MASALALARI - Xo‘janiyazov, E.; Yusupova, G.A. (SCIENCE and SOCIETY, 2020)
The Uzbek and Karakalpak languages, belonging to the same language system, influence and interact with each other. These connections can be seen on all levels of these languages, especially it is seen well on the lexical level. The author of the article studies the issues-how and on what level these languages influence on each other for the years of Independence.